ANALISIS PERBANDINGAN PROTOCOL ROUTING AD HOC UNTUK JARINGAN BERSKALA BESAR - Dy, Jap Fen; Jusak, Jusak; Triwidyastuti, Yosefine (Journal of Control and Network Systems, 2015)
Wireless network tecnology has long been discovered. Currently, it is evident that there are significant growth in the number of tools that utilize this technology. One of the impacts of wireless networks is the Ad hoc technology,  which is commonly called the Ad hoc network. Ad hoc is a wireless network that contains a group of nodes that communicate each other. The Ad hoc  networks do not require any infrastructure. The Ad hoc technology has been used in various ways, such as military operations, or personal communication i.e. phone, PDA or laptop. This research will simulate the  Ad hoc protocol routing in large scale network. Performance analysis is done by comparing routing protocol AODV (Ad hoc On-Demand Distance Vector)  and DSR (Dynamic Source Routing) based on delay, PLR(Packet Loss Ratio), PDR(Packet delivery ratio), packet drop, bandwidth utilization and NRL(Normalized routing load) for 10 nodes to 70 nodes.Based on our study it is shown that DSR has better performance in  terms of delay, packet loss dan normalized routing load. On the other hand AODV has better performance in terms of bandwidth utilization for large scale network.